IMPACT OF WORKING CAPITAL MANAGEMENT ON FIRM’S PROFITABILITY: A STUDY OF NUMALIGARH REFINERY LTD., INDIA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2021)
The paper is an attempt to assess the impact  of working capital management on liquidity  and profitability (ROI) of the company and  to establish the linear relationship between  liquidity and profitability with the help of multi  regression model. For assessing the impact, a  13 year period has been considered. The study  is based on secondary data collected from  published annual reports of the refinery which  are analyzed with the help of correlation and  ANOVA test. The study focuses on the factors  which are responsible for changing the working  capital of the refinery which as a result influences  the profitability of the refinery. The study shows  the result of different independent variables on  profitability of the refinery.
Keywords: liquidity; profitability; ROI; working capital